How Does Psychological Empowerment Prevent Emotional Exhaustion? Psychological Safety and Organizational Embeddedness as Mediators - Zhou, Hao; Chen, Jingyi (Frontiers in Psychology, 2021)
Emotional exhaustion in the workplace can cause employees psychological and physical health problems, affect work performance, and create burdens for the organization. Existing studies have demonstrated that psychological empowerment helps reduce emotional exhaustion. This study explores the internal mechanism of this relationship. Drawing on conservation of resources (COR) theory, we advance a dual mediation model to explain how high psychological empowerment results in low emotional exhaustion, by increasing psychological safety and organizational embeddedness. Data were collected from 226 on-the-job MBA students at a university in western China. The results demonstrate that psychological safety and organizational embeddedness play mediating roles in the negative relationship between psychological empowerment and emotional exhaustion. The study provides a systematic view of the negative effect that psychological empowerment has on emotional exhaustion. The paper also discusses theoretical contributions, practical implications, and future directions.